Attitudes of physicians, nurses and pharmacists concerning the development of clinical pharmacy activities in a university hospital - Čufar Andreja; Locatelli Igor; Mrhar Aleš (Acta Pharmaceutica)
It is essential to identify the expectations of physicians and nurses regarding clinical pharmacy (CP) services before its introduction in a hospital, because it is known that their expectations can substantially differ from the pharmacists’ point of view. Agreement of leading physicians, nurses and clinical pharmacists about the importance of CP activities in the hospital was evaluated using five point Likert scale questionnaire. Two groups of CP activities were set; the activities related to the hospital system (first group) and the activities connected with an individual patient (second group). Total mean score of agreement of physicians with the first and second group of CP activities is 4.28 and 3.73, respectively, while these scores are lower for nurses (3.87 and 3.38 for the first and second group, respectively). Pharmacists’ total mean scores are highest, 4.57 and 4.23 for the first and second group, respectively.